The Good, the Bad, and the Lethal: Gene Expression and Metabolomics Reveal Physiological Mechanisms Underlying Chronic Thermal Effects in Mayfly Larvae (Neocloeon triangulifer) - Chou, Hsuan; Pathmasiri, Wimal; Deese-spruill, Jocelin; Sumner, Susan J.; Jima, Dereje D.; Funk, David H.; Jackson, John K.; Sweeney, Bernard W.; Buchwalter, David B. (Frontiers in Ecology and Evolution, 2018)
Temperature dictates the performance of aquatic ectotherms. However, the physiological and biochemical processes that drive thermally-mediated life history patterns (and limits) remain poorly understood because they are rarely studied simultaneously. In our previous work, we have established life history outcomes (e.g. survivorship, development time, growth rates and fitness) in mayflies (Neocloeon triangulifer) reared at static temperatures ranging from 14°C - 30°C at 2°C intervals. In this study, we conducted biochemical measurements (RT-qPCR of select genes and targeted, quantitative metabolomic profiling) on N. triangulifer mature larvae reared at temperatures associated with excellent survival and fitness (22-24°C), compromised survival and fitness (28°C), and chronic lethality (30°C -larvae survived for a few weeks but failed to emerge to adulthood). Patterns of gene expression were similar to those observed in acute ramping experiments reported previously: larvae reared at 30°C resulted in significant upregulation in the thermally responsive gene HEAT SHOCK PROTEIN 90 (HSP90) but no significant changes in hypoxia responsive genes (EGG LAYING DEFECTIVE 9 (EGL-9) and LACTATE DEHYDROGENASE (LDH)). Additionally, primers for genes associated with energy: INSULIN RECEPTOR (IR), mechanistic TARGET OF RAPAMYCIN (mTOR) and TREHALOSE 6 PHOSPHATE SYNTHASE (T6PS) were developed for this study. IR and mTOR were significantly upregulated while T6PS showed trend of downregulation in larvae reared at 30°C. Metabolomic profiles revealed general depletion of lipids and acylcarnitines in larvae exposed to chronic thermal stress, suggesting that larvae were energetically challenged despite continuous access to food. For example, concentrations of lysoPhosphatidylcholine (lysoPC) a C20:3 decreased as fitness decreased with increasing temperature (2.3 fold and 2.4 fold at 28 and 30°C relative to controls). Tissue concentrations of the biogenic amine histamine increased 2.1 and 3.1 fold with increasing temperature, and were strongly and negatively correlated with performance. Thus, both histamine and lysoPC a C20:3 are potential biomarkers of thermal stress. Taken together, our results primarily associate energetic challenge with thermally mediated fitness reduction in N. triangulifer.